Dinner with Olivia - Sollinger, Emily; Wolek, Guy; Nickelodeon (Television network) (London : Simon and Schuster, 2010)
Olivia invites Francine over for a spaghetti dinner, but she is nervous that her brothers' poor table manners will be offensive.
"Based on the TV series Olivia as seen on Nickelodeon"--T.p. verso.
2.9
K-3
Keywords: Dinners and dining -- Juvenile fiction; Olivia (Fictitious character : Falconer) -- Juvenile fiction; Table etiquette -- Juvenile fiction; Dinners and dining -- Fiction; Olivia (Fictitious character : Falconer) -- Fiction; Table etiquette -- Fiction; Dinners -- Fiction; Olivia (Fictional character : Falconer) -- Fiction; Radio and television novels; Table etiquette -- Fiction; Picture books for children; Radio and television novels